PENINGKATAN KOMPETENSI PROFESIONAL GURU DALAM MENYUSUN LAPORAN PENELITIAN TINDAKAN KELAS MELALUI MODEL PEMBINAAN CLCK (CONTOH, LATIHAN, CONTROL, KERJA MANDIRI) BERBASIS MENTORING DI SMAN 10 PADANG - Masril Masril (JURNAL MANAJEMEN PENDIDIKAN, 2017)
ABSTRACT This study aims to describe and obtain information about the improvement of professional competence of teachers in preparing classroom action research reports through CLCK development model (Example, Exercise, Control, Self Employment) based mentoring in SMAN 10 Padang. This research is a school action research with research procedure including planning, action, obeservasi and reflection. This study consists of two cycles with four meetings. The subjects consisted of 13 teachers of SMAN 10 Padang. Research data was collected using obeservation sheets. Data were analyzed using percentages. The results showed that mentoring model based on CLCK can improve teacher ability in preparing class action research report in SMAN 10 Padang. Analysis on the quality of PTK reports made by teachers indicates that the professional competence of teachers in preparing classroom action research reports increases from cycle I to cycle II. Teacher professional competence in preparing class action research report on cycle I is 77,69 (enough) increase to 84,69 (good) in cycle II with increase of equal to 7.00 points. Keywords: Professional Teacher Competency, PTK Report, CLCK mentoring based mentoring model